2013
DOI: 10.1017/s1751731113001146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water restriction on growth performance, feed nutrient digestibility, carcass and meat traits of rabbits

Abstract: The study investigates the effects of a post-weaning water restriction on performance, nutrient digestibility, carcass traits and meat quality of 84-day-old rabbits. A total of 1388 weaned rabbits (35 days) were randomly divided into two groups on the basis of BW and sex. The two groups were fed the same diets ad libitum both in the post-weaning (35 to 60 days) and fattening (61 to 84 days) periods. In the post-weaning period, one group (AL) also received drinking water ad libitum, whereas the other (WR) had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
(19 reference statements)
2
20
0
Order By: Relevance
“…In line with other authors (Tumova et al, 2006;Bovera et al, 2013) who observed no effect of limited feed intake on physical and chemical characteristics of meat, in this study the feed restriction did not influence meat quality and tended only to reduce the meat fat content, which corresponded with slightly higher cooking losses, whereas the tendency towards an higher pH in L-M was so weak as to be considered negligible.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In line with other authors (Tumova et al, 2006;Bovera et al, 2013) who observed no effect of limited feed intake on physical and chemical characteristics of meat, in this study the feed restriction did not influence meat quality and tended only to reduce the meat fat content, which corresponded with slightly higher cooking losses, whereas the tendency towards an higher pH in L-M was so weak as to be considered negligible.…”
supporting
confidence: 91%
“…As reported in the review of Gidenne et al (2012), the methods used to control rabbit feed intake differ in terms of duration and intensity, but commonly involve a limited feeding time or a reduced supply of feed; studies have also examined energy (Szendrő et al, 2008;Metzger et al, 2009;Pascual et al, 2014) and water restriction (Bovera et al, 2013). Nevertheless, only Matics et al (2008) studied the effects of a post-weaning feed restriction compared directly with the dietary use of antibiotics, whereas there is a lack of information regarding these effects in relation to the growth potential of rabbits genotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding strategies are the most practical ways to alleviate the negative effects of high environmental temperatures on animal performance, health status and immunity (Attia et al 2009;Bovera et al 2013;Akbarian et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors, such as light and temperature, are known to affect performance in broilers (Attia et al, 2011;Bovera et al, 2013). In many areas, broilers are commonly provided continuous or near continuous illumination.…”
Section: Introductionmentioning
confidence: 99%